Indonesia Air Space Liberalization towards ASEAN Community 2015 - Arafah, Adhy Riadhy (UI Scholars Hub, 2011)
ASEAN integration gives consequence in regional and national aviation. As a part of ASEAN Economy Community (AEC) programme, ASEAN Aviation proclaimed Open Sky as a policy for liberalization. In addition, the policy has dramatically implication in Indonesia aviation market including passenger, destination and facilities which Indonesia is not ready yet. Air space liberalization covers 3rd, 4th, and 5th freedom of the air and some soft right for facilities. For Indonesia these are no easy to face it. Indonesia government with all the limitation has to analyze and raise the capability of its human resources and facilities with international standard. In the other hand, Singapore with Singaporean airlines and some facilities are ready for enforcing the item of this policy. Furthermore, ASEAN integration should have seen from whole aspect, not only political reason as a tool for achieving international recognition but also the readiness of the members.